(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
One of the most glaring environmental issues currently facing industrialized nations isindustrial pollution, which also affects the majority of recently industrializing economies. The industrialstructure of India has seen numerous changes, particularly after the economic reforms. However, nosignificant environmental reforms were launched in India to account for the effects of changingindustrial patterns on the environment. Analysis of the environmental effects of India’s industrial sectoris so necessary. Since different sectors produce pollution at varying intensities, this work has firstexamined the make-up of the industrial structure. We calculated the changes in the pollution load ofIndian companies using the Industrial Pollution Projection model developed by the World Bank forcalculating pollution load in developing nations without access to continuous industrial pollution data.Finally, we suggest policy changes that are required to promote resource substitution away from finiteresources, adoption of technology and practices that minimize environmental effect, and more efficientresource usage. Industrial pollution is seen as a significant contributor to environmental contamination.It degrades the environment and costs society significantly while also endangering the health and safetyof people. The main polluting industries include petroleum, sugar, tanning, glass, cement, glass, andplastic. This important problem of industrial pollution receives little or no attention. Many industrialsectors do not employ a systematic method for the proper drainage and disposal of their hazardouseffluent. Since the industrial sector is responsible for over 50 of the environmental contamination, itshould be held accountable for its duties regarding proper waste effluent treatment.